Sex differences in the association of fasting and postchallenge glucose levels with grip strength among older adults: the Rancho Bernardo Study. Issue 1 (4th May 2015) - Kalyani, Rita Rastogi; Kim, Catherine; Ferrucci, Luigi; Laughlin, Gail A; Kritz-Silverstein, Donna; Kong, Shengchun; Nan, Bin; Barrett-Connor, Elizabeth
Abstract : Objective: Persons with diabetes have accelerated muscle loss. The association of fasting and postchallenge glucose levels per se to grip strength, a clinical marker of poor physical function, and potential sex differences in this relationship has not been previously described. Design: Longitudinal cohort. Setting: USA. Participants: Participants were community-dwelling older adults (mean age 71.3 years) without self-reported diabetes and/or use of diabetes medication with glucose measured at baseline (1992–1996). Measurements: Fasting plasma glucose (FPG) was measured in 1019 women and 636 men. Two-hour glucose (2HG) levels after a 75 g oral glucose tolerance test were also available (women, n=870; men, n=559). Dominant hand grip strength was assessed using a hand-held dynamometer at 3.0±1.6 visits over a median 7.0 years. Mixed linear models examined the association of baseline glucose levels with grip strength, accounting for repeated visits, and adjusting for covariates. Results: Sex-specific FPG quartiles were associated with unadjusted differences in grip strength among women (p=0.03) but not men (p=0.50). However, in men, adjusting for age, education, height, weight, peripheral neuropathy, physical activity, and comorbidities, each SD (SD=17 mg/dL) higher FPG was associated with persistently lower grip strength (−0.44±0.22 kg, p=0.049); 2HG (SD=50 mg/dL) was unrelated to grip strength (−0.39±0.25 kg, p=0.13). In women, neither FPG (SD=16 mg/dL) nor 2HG (SD=45 mg/dL) was associated with grip strength (0.02±0.12 kg, p=0.90; and −0.20±0.14 kg, p=0.14; respectively) after adjustment. The rate of change in grip strength did not differ across FPG or 2HG quartiles in either sex. Conclusions: In age-adjusted analyses, elevated fasting glucose levels are associated with persistently lower grip strength in older men, but not women. Future studies are needed to elucidate reasons for these sex differences and may provide further insight into accelerated loss of muscle function as a complication of diabetes in older adults.